Robust Crazy Ant (suggested common name) Nylanderia bourbonica (Forel) (Insecta: Hymenoptera: Formicidae: Formicinae) - Jason Williams; Andrea Lucky (EDIS, 2017)
Originally published on the Featured Creatured website at http://entnemdept.ufl.edu/creatures/urban/ants/robust_crazy_ant.htm